Weighted Equilibrium States at Zero Temperature. Issue 2 (2nd July 2020) - Mesón, Alejandro; Vericat, Fernando
Abstract: Weighted thermodynamic and multifractal formalism for finite alphabet subshifts have been presented by Barral and Feng ( Asian J. Math, 16, 319–352, 2012). Here we analyze the problem of finding weighted equilibrium states for infinite countable shifts. Also we study the problem of "zero temperature" which consists into consider a sequence of equilibrium states depending of a parameter, interpreted in a Statistical Mechanics context as "the inverse of the temperature", and prove the existence of accumulation points of such a sequence.